A step forward in addressing cancer survivorship in the Asia-Pacific region. Issue 1 (December 2017) - Chan, Raymond; Chan, Alexandre; Yates, Patsy; Molassiotis, Alex
Abstract Cancer survivorship is being increasingly recognized as an important component of cancer care. This commentary reviews the key findings reported in the recentBMC Medicine publication of the ACTION study, which focuses on the health-related quality of life and psychological distress in 5249 cancer survivors in eight low- and middle-income countries in Southeast Asia. The study identified that more than one-third of survivors experience at least mild levels of anxiety and depressive symptoms and that poorer outcomes in quality of life, anxiety, and depressive symptoms are linked to a number of clinical and demographic factors. Such data provides an important foundation to inform cancer policy and service planning in Asia. Future research efforts are required to further understand the needs of cancer survivors in this region and determine interventions to improve outcomes for this population. Please see related article:http://bmcmedicine.biomedcentral.com/articles/10.1186/s12916-016-0768-2 .